Thermoelastic stability of thick imperfect functionally graded plates - Tung, Hoang Van; Duc, Nguyen Dinh (Vietnam Journal of Mechanics, 2010)
This paper investigates buckling of thick functionally graded plates with initial geometrical imperfection under thermal loadings. The equilibrium, stability, and compatibility equations of an imperfect functionally graded plate are derived using the third order shear deformation theory. Material properties are assumed to be temperature-independent and graded in the thickness direction according to a simple power law distribution in terms of the thickness coordinate variable. By Galerkin method, the resulting equations are solved to obtain closed-form solutions of critical buckling temperature difference. Two types of thermal loading, uniform temperature rise and nonlinear temperature change across the thickness are considered. Buckling analysis for a simply supported rectangular imperfect functionally graded plate shows effects of geometry and material parameters, shear deformation and imperfection on critical buckling temperature.